Human sensorimotor beta event characteristics and aperiodic signal are highly heritable - Pauls, K Amande M.; Salmela, Elina; Korsun, Olesia; Kujala, Jan; Salmelin, Riitta; Renvall, Hanna (Society for Neuroscience, 2025)
Individuals' phenotypes, including the brain's structure and function, are largely determined by genes and their interplay. The resting brain generates salient rhythmic patterns that can be characterized non-invasively using functional neuroimaging such as magnetoencephalography (MEG). One of these rhythms, the somatomotor ('rolandic') beta rhythm, shows intermittent high amplitude 'events' that predict behavior across tasks and species. Beta rhythm is altered in neurological disease. The aperiodic ('1/f') signal present in electrophysiological recordings is also modulated by some neurological conditions and aging. Both sensorimotor beta and aperiodic signal could thus serve as biomarkers of sensorimotor function. Knowledge about the extent to which these brain functional measures are heritable could shed light on the mechanisms underlying their generation. We investigated the heritability and variability of human spontaneous sensorimotor beta rhythm events and aperiodic activity in 210 healthy male and female adult siblings' spontaneous MEG activity. The most heritable trait was the aperiodic 1/f signal, with a heritability of 0.87 in the right hemisphere. Time-resolved beta event amplitude parameters were also highly heritable, whereas the heritabilities for overall beta power, peak frequency and measures of event duration remained nonsignificant. Human sensorimotor neural activity can thus be dissected into different components with variable heritability. We postulate that these differences partially reflect different underlying signal generating mechanisms. The 1/f signal and beta event amplitude measures may depend more on fixed, anatomical parameters, whereas beta event duration and its modulation reflect dynamic characteristics, guiding their use as potential disease biomarkers.Significance statement The resting brain shows a prominent, highly modulated beta-range rhythm closely linked to sensorimotor function in health and disease. We investigated the heritability of human spontaneous sensorimotor beta rhythm and its different components in a large cohort of 210 siblings' MEG data. We find that particularly beta event amplitude and its variation as well as aperiodic signal characteristics are highly heritable. The study demonstrates that time-resolved electrophysiological measures of spontaneous human sensorimotor brain activity are determined to a significant degree by genes. We discuss the findings in the context of known and postulated structural underpinnings of MEG signal generation, to highlight their translational relevance. The findings have clinical implications, e.g, when considering sensorimotor beta alterations as biomarkers of neurological disease.